At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine which expression is equivalent to [tex]\((x+5)(2x^2 + 8)\)[/tex], we need to expand the given expression using the distributive property.
The distributive property states that [tex]\(a(b + c) = ab + ac\)[/tex]. Applying this property to our expression [tex]\((x+5)(2x^2 + 8)\)[/tex], we have:
[tex]\[ (x+5)(2x^2 + 8) = (x+5) \cdot 2x^2 + (x+5) \cdot 8 \][/tex]
Let's break this down step by step:
1. Distribute [tex]\( (x+5) \)[/tex] to [tex]\( 2x^2 \)[/tex]:
[tex]\[ (x+5) \cdot 2x^2 = 2x^2(x+5) = 2x^2 \cdot x + 2x^2 \cdot 5 = 2x^3 + 10x^2 \][/tex]
2. Distribute [tex]\( (x+5) \)[/tex] to [tex]\( 8 \)[/tex]:
[tex]\[ (x+5) \cdot 8 = 8(x+5) = 8x + 40 \][/tex]
So, combining these results:
[tex]\[ 2x^3 + 10x^2 + 8x + 40 \][/tex]
Now, let's examine the choices given:
A. [tex]\((x+5)(2x) + (x+5)(8)\)[/tex]
Expanding this:
[tex]\[ (x+5) \cdot 2x = 2x(x+5) = 2x^2+10x \][/tex]
[tex]\[ (x+5) \cdot 8 = 8(x+5) = 8x + 40 \][/tex]
Combining these:
[tex]\[ 2x^2 + 10x + 8x + 40 = 2x^2 + 18x + 40 \][/tex]
This is not the same as our expanded expression.
B. [tex]\((x+5)(2x^2) + (x+5)(8)\)[/tex]
Expanding this:
[tex]\[ (x+5) \cdot 2x^2 = 2x^2(x+5) = 2x^3 + 10x^2 \][/tex]
[tex]\[ (x+5) \cdot 8 = 8(x+5) = 8x + 40 \][/tex]
Combining these:
[tex]\[ 2x^3 + 10x^2 + 8x + 40 \][/tex]
This matches our expanded expression.
C. [tex]\((x+5)(2x^2) \cdot (x+5)(8)\)[/tex]
This is not distributive. It means we are multiplying the two resultant quantities, which is not correct.
D. [tex]\((x+5)(2x) \cdot (x+5)(8)\)[/tex]
This is incorrect for the same reason as C; it's a multiplication of two terms rather than distribution.
The correct choice is:
B. [tex]\((x+5)(2x^2) + (x+5)(8)\)[/tex]
The distributive property states that [tex]\(a(b + c) = ab + ac\)[/tex]. Applying this property to our expression [tex]\((x+5)(2x^2 + 8)\)[/tex], we have:
[tex]\[ (x+5)(2x^2 + 8) = (x+5) \cdot 2x^2 + (x+5) \cdot 8 \][/tex]
Let's break this down step by step:
1. Distribute [tex]\( (x+5) \)[/tex] to [tex]\( 2x^2 \)[/tex]:
[tex]\[ (x+5) \cdot 2x^2 = 2x^2(x+5) = 2x^2 \cdot x + 2x^2 \cdot 5 = 2x^3 + 10x^2 \][/tex]
2. Distribute [tex]\( (x+5) \)[/tex] to [tex]\( 8 \)[/tex]:
[tex]\[ (x+5) \cdot 8 = 8(x+5) = 8x + 40 \][/tex]
So, combining these results:
[tex]\[ 2x^3 + 10x^2 + 8x + 40 \][/tex]
Now, let's examine the choices given:
A. [tex]\((x+5)(2x) + (x+5)(8)\)[/tex]
Expanding this:
[tex]\[ (x+5) \cdot 2x = 2x(x+5) = 2x^2+10x \][/tex]
[tex]\[ (x+5) \cdot 8 = 8(x+5) = 8x + 40 \][/tex]
Combining these:
[tex]\[ 2x^2 + 10x + 8x + 40 = 2x^2 + 18x + 40 \][/tex]
This is not the same as our expanded expression.
B. [tex]\((x+5)(2x^2) + (x+5)(8)\)[/tex]
Expanding this:
[tex]\[ (x+5) \cdot 2x^2 = 2x^2(x+5) = 2x^3 + 10x^2 \][/tex]
[tex]\[ (x+5) \cdot 8 = 8(x+5) = 8x + 40 \][/tex]
Combining these:
[tex]\[ 2x^3 + 10x^2 + 8x + 40 \][/tex]
This matches our expanded expression.
C. [tex]\((x+5)(2x^2) \cdot (x+5)(8)\)[/tex]
This is not distributive. It means we are multiplying the two resultant quantities, which is not correct.
D. [tex]\((x+5)(2x) \cdot (x+5)(8)\)[/tex]
This is incorrect for the same reason as C; it's a multiplication of two terms rather than distribution.
The correct choice is:
B. [tex]\((x+5)(2x^2) + (x+5)(8)\)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.